1992
DOI: 10.1111/j.1365-313x.1992.00181.x
|View full text |Cite
|
Sign up to set email alerts
|

Vicilin with carboxy-terminal KDEL is retained in the endoplasmic reticulum and accumulates to high levels in the leaves of transgenic plants

Abstract: Gene constructs were designed to test the effect of the endoplasmic reticulum (El?)-targeting signal, KDEL, on the level of accumulation of a foreign protein in transgenic plants. The gene for the pea seed protein vicilin was modified by the addition of a sequence coding for this tetrapeptide at its carboxyl terminus. The altered gene was placed under the control of a CaMV 35s promoter and its expression in the leaves of both tobacco and lucerne (alfalfa) was compared with that of an equivalent vicilin constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
75
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 38 publications
10
75
2
Order By: Relevance
“…In support of this hypothesis is the fact that retention of the vacuolar pea vicilin protein in the ER when an ER retention signal is engineered on to the protein stabilizes the modified protein 100-fold over unmodified vicilin protein (Wandelt et al, 1992). The stability of the P-phaseolin protein in mature seeds is probably due to the fact that the protein is now shunted to differentiated protein bodies that do not have active proteases.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…In support of this hypothesis is the fact that retention of the vacuolar pea vicilin protein in the ER when an ER retention signal is engineered on to the protein stabilizes the modified protein 100-fold over unmodified vicilin protein (Wandelt et al, 1992). The stability of the P-phaseolin protein in mature seeds is probably due to the fact that the protein is now shunted to differentiated protein bodies that do not have active proteases.…”
Section: Discussionmentioning
confidence: 48%
“…ER-retained proteins would thus be more stable in nonseed tissues simply because they are not exposed to vacuolar proteases. In support of this hypothesis is the fact that retention of the vacuolar pea vicilin protein in the ER by engineering a ER retention signal onto the protein stabilized the modified protein 100-fold over unmodified vicilin protein when synthesized in leaves of transgenic plants (Wandelt et al, 1992). However, many vacuolar proteins such as the pea lectin (Edwards et al, 1991), barley lectin (Wilkins et al, 1990), and cowpea trypsin inhibitor (Hilder et al, 1987) have been shown to be stable in leaves of transgenic plants.…”
mentioning
confidence: 83%
“…This process involves cleavage of the signal peptide and translocation of the protein through the membrane into the cisternal space of the ER. The protein is retained in the ER lumen if it has a carboxy-terminal domain with the four amino acids HDEL or KDEL (Wandelt et al, 1992). Correctly folded proteins then enter the Golgi.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we wanted to examine the effects of localizing TDC to the chloroplast, the site of biosynthesis of the enzyme's natural substrate, l-Trp (Radwanski and Last, 1995). We also studied the effects of targeting TDC to the endoplasmic reticulum (ER) because it has been demonstrated that targeting proteins to the ER (Iturriaga et al, 1989;Wandelt et al, 1992;Boevink et al, 1996) significantly enhances accumulation of the respective recombinant protein in plant cells (Fiedler et al, 1997;Gomord et al, 1997;Fischer et al, 1999).…”
mentioning
confidence: 99%
“…In particular, we wanted to examine the effects of localizing TDC to the chloroplast, the site of biosynthesis of the enzyme's natural substrate, l-Trp (Radwanski and Last, 1995). We also studied the effects of targeting TDC to the endoplasmic reticulum (ER) because it has been demonstrated that targeting proteins to the ER (Iturriaga et al, 1989;Wandelt et al, 1992; Boevink et al, 1996) significantly enhances accumulation of the respective recombinant protein in plant cells (Fiedler et al, 1997; Gomord et al., 1997;Fischer et al, 1999).TDC is a cytosolic enzyme in TIA-producing plants such as C. roseus (De Luca and Cutler, 1987;Stevens et al, 1993), and ideally, studies on localization of TDC should be carried out using transgenic material from the plant expressing TDC as part of the pathway of interest; in our case, TIA biosynthesis in C. roseus. However, although transgenic undifferentiated C. roseus cell cultures can be recovered with relative ease, TIA biosynthesis is severely impeded in such cultures.…”
mentioning
confidence: 99%